The Rutgers Alcohol Problem Index: Measurement Equivalence among College Students in the U.S. and Mexico - Armenta, Brian E. (Psychol Assess, 2018)
The Rutgers Alcohol Problem Index (RAPI) is widely used to assess alcohol-related problems among college students within the U.S. and internationally. Despite its wide usage, whether the RAPI similarly assesses alcohol-related problems among students in different countries has not been established. We begin to address this issue by evaluating responses to the RAPI for measurement equivalence across college students in the U.S. (European Americans and Mexican Americans, treated as separate groups) and Mexico (Mexicans). Towards this end, we evaluated the RAPI for Differential Item Functioning (DIF) within an item response theory framework. Our results showed DIF for six item severities, all but one of which differed as a function of country (U.S. vs. Mexico). Additional analyses showed that using a latent RAPI variable with no DIF assumed had no substantive consequences in terms of group mean differences and zero-order correlations with self-reported drinking behaviors. Similarly, when using observed RAPI scale scores, there were no substantive differences in terms of correlations. The observed scale scores, however, led to inaccurate mean comparisons. Based on our results, we recommend that scholars model the RAPI as a latent variable when conducting analyses.